Stop for tea? Enzyme inhibitors from tea – what good are they?. (29th December 2016) - Zhao, Min; Li, Da; Ye, Jian‐Hui; Zheng, Xin‐Qiang; Liang, Yue‐Rong; Lu, Jian‐Liang
Summary: Tea possesses many bioactive components including polyphenols, theanine and caffeine. Inhibitory effect of these components on the various enzymes involved in some chronic diseases was reviewed in this study. Many studies revealed that anti‐obesity of tea was mainly ascribed to the polyphenols which could inhibit the activity of the enzymes related to diet metabolism such as α‐amylase, α‐glucosidase and lipase. Inhibitory effect of catechins and caffeine against β‐ and γ‐secretase, acetylcholinesterase, protein kinase C and histone deacetylase might be responsible for the prevention from nervous system diseases. Cytochrome P450 enzymes, cytosolic sulfotransferases, cyclooxygenase‐2 and phosphoinositide‐3‐kinase could be efficiently suppressed by catechins, which would decrease the risk of cancer initiation and proliferation; theanine could lower the activity of some anticarcinogen‐activated enzymes and alleviate the adverse effect of cancer cure. Catechins and caffeine exhibited significant inhibition against the matrix metalloproteinases, histidine decarboxylase and many kinases related to inflammation. Thus, catechins, theanine and caffeine might be employed as inhibitors of the enzymes associated with these chronic diseases. Abstract : TPs, caffeine and theanine in tea can inhibit the enzymes involved in obesity, AD&PD, cancers and inflammation, thus improve these diseases and provide beneficial effects to human health. PTP1B: protein tyrosine phosphatase 1B; iNOS: inducible nitric oxide synthase; HDAC: histone deacetylase; CYPs: cytochrome P450 enzymes; SULTs: sulfotransferases; COX‐2: cyclooxygenase‐2; MMPs: matrix metalloproteinases; HDC: histidine decarboxylase.